Cribellate Spider, Metaltella simoni (Keyserling) (Arachnida: Araneae: Amphinectidae) - Glavis B. Edwards (EDIS, 2005)
Metaltella simoni (Keyserling) is a relatively recent introduction to the Florida spider fauna. Although it is generally inconspicuous, M. simoni may be a threat to extirpate the Florida population of our native amaurobioid species, Titanoeca brunnea Emerton. This document is EENY-322 (originally published as DPI Entomology Circular 354), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2004.